2010
DOI: 10.1126/science.1194980
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Type I Metacaspases Control Cell Death

Abstract: The Yin and Yang of Plant Caspases The function of plant metacaspases, identified by limited sequence homology to the animal caspases that control cell death, has remained elusive. Coll et al. (p. 1393 ) have now elucidated the actions of two metacaspases in the small plant Arabidopsis . One metacaspase, AtMC1, promoted cell death, and the other, AtMC2, acted antagonistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
353
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(381 citation statements)
references
References 32 publications
11
353
2
4
Order By: Relevance
“…10,31,32 In contrast, the role of trypanosomatid metacaspases seems to be less certain. Overexpression of full-length TcMCA5 in T. cruzi renders epimastigotes more susceptible to FHS-induced cell death, 20 and Gonzá lez et al 30 have shown that L. major metacaspase can replace yeast metacaspase in its pro-cell death action during ageing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,31,32 In contrast, the role of trypanosomatid metacaspases seems to be less certain. Overexpression of full-length TcMCA5 in T. cruzi renders epimastigotes more susceptible to FHS-induced cell death, 20 and Gonzá lez et al 30 have shown that L. major metacaspase can replace yeast metacaspase in its pro-cell death action during ageing.…”
Section: Discussionmentioning
confidence: 99%
“…5 Their substrate specificity is for basic residues at P1 position, making them unable to cleave caspase substrates. 6 Evidences suggest that metacaspases modulate cell death, [7][8][9][10][11] cell cycle progression [12][13][14] and protein aggregation, 15 but there is still controversy about their functions and their relation with caspases. [16][17][18] The fact that metacaspases are not present in humans and fulfil important roles in trypanosomatids make them attractive drug targets, and a first series of inhibitors with trypanocidal activity has been developed recently.…”
mentioning
confidence: 99%
“…Thus, the processed BAG6 generated from aspartyl protease cleavage correlates with plant resistance via autophagy. Several genes have been shown to modulate cell death and potentially alter immune responses in Arabidopsis, including LOL1 (Epple et al, 2003), LSD1 (Torres et al, 2005), and metacaspases (Coll et al, 2010). Premature senescence and spreading lesions also occur in autophagydeficient plants as a result of accumulation of ubiquitinated proteins and with ER stress (Coll et al, 2014;Munch et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The hypersensitive response is often used as a visible measure of an effective defense response and a hallmark of immunity, however, caution must be taken as the hypersensitive response is not essential and immunity can be achieved without an outcome of cell death [14].…”
Section: Host Immunity In Plant-parasite Interactionsmentioning
confidence: 99%
“…The putative defense gene PR-1a is one example where failure to properly account for 14 developmental context could lead to misinterpretation. PR-1a was up-regulated systemically in leaves of tomato plants infested with root-knot nematodes, but there was no differential expression in root tissues [34].…”
Section: Defense Marker Genes: a Question Of Contextmentioning
confidence: 99%